Rheological comparison of sputum and reconstituted airway epithelium mucus - Lydia Esteban Enjuto; Vassylia Taty Poaty; Mendy Bouveret; Huang Song; Samuel Constant; Jérémy Patarin (Scientific Reports)
Abstract Pulmonary mucus serves as a crucial protective barrier in the respiratory tract, defending against pathogens and contributing to effective clearance mechanisms. In Muco Obstructive Pulmonary Diseases (MOPD), abnormal rheological properties lead to highly viscous mucus, fostering chronic infections and exacerbations. While prior research has linked mucus viscoelasticity to its mucin content, the variability in MOPD patients implies the involvement of other factors. To isolate these effects, mucus produced by epithelia reconstituted in vitro serves as a powerful versatile model for mucin research. This study characterises the rheology of mucus collected from Air-Liquid Interface (ALI) cultures and compares it to sputum samples from MOPD patients, demonstrating that macrorheology with cone-plate geometries is a reproducible method for analysing small mucus quantities from ALI cultures. While sputum samples exhibit similarities in rigidity with ALI mucus, they also display structural differences and variations in their response to substantial deformations. The study highlights the importance of understanding mucus behaviour under large deformations, emphasising the role of ALI cultures as a controlled environment for conducting detailed studies.